2018
DOI: 10.11648/j.jfns.20180601.12
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Mineral Composition Variability in Ethiopian Yam (<i>Dioscorea</i> spp)

Abstract: Abstract:Fourty two yam (Dioscorea species) sprouted tubers were collected from six different major growing regions of Ethiopia and planted at Hawasa Agricultural Research Center. The Dioscorea species considered in this study were D. bulbifera, D. abyssinica, D. cayenensis, D. rotundata, D. praehensilis, and D. alata. Five Proximate compositions (moisture, ash, crude fat, crude protein and crude fibre) and four minerals content (calcium, phosphorous, zinc and iron) were determined from 100g yam tubers at Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 4 publications
0
15
2
1
Order By: Relevance
“…Both blanching and boiling might enhance the loss of water‐soluble components and increase the percentage of macromolecules rich in dietary fiber. The TF of the raw and pretreated anchote flours (6.34 – 10.92 g/100 g) was higher than values reported for other tuberous crops (potato, sweet potato, cassava, cocoyam, and yam) by several previous researchers (Aathira & Siddhuraju, 2017; Baah et al., 2009; Bekele & Bekele, 2018; Egbuonu & Nzewi, 2016; Harijono et al., 2013; Lewu et al., 2009; Nascimento & Canteri, 2018; Onodu, Culas, & Nwose, 2018; Ukom et al., 2018). Therefore, anchote flour can be used to enhance dietary fiber by incorporating into other foods or by aiding in the formulation of diets for people with diabetes and other health‐conscious individuals.…”
Section: Resultscontrasting
confidence: 53%
See 3 more Smart Citations
“…Both blanching and boiling might enhance the loss of water‐soluble components and increase the percentage of macromolecules rich in dietary fiber. The TF of the raw and pretreated anchote flours (6.34 – 10.92 g/100 g) was higher than values reported for other tuberous crops (potato, sweet potato, cassava, cocoyam, and yam) by several previous researchers (Aathira & Siddhuraju, 2017; Baah et al., 2009; Bekele & Bekele, 2018; Egbuonu & Nzewi, 2016; Harijono et al., 2013; Lewu et al., 2009; Nascimento & Canteri, 2018; Onodu, Culas, & Nwose, 2018; Ukom et al., 2018). Therefore, anchote flour can be used to enhance dietary fiber by incorporating into other foods or by aiding in the formulation of diets for people with diabetes and other health‐conscious individuals.…”
Section: Resultscontrasting
confidence: 53%
“…The variations may be due to variety, growing ecology, tuber maturity, and treatment methods used (Abera & Haile, 2015; Ayalew, 2016; Shebabaw, 2013). It was observed that the anchote flour contains reasonably higher Ca compared to other common tuberous flours such as sweet potato (50.28–110.53 mg/100 g), potato (9 mg/100 g), and yam (31.02–118.8 mg/100 g) (Bekele & Bekele, 2018; Koua, Zoué1, T L R M…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, several scientific studies have evaluated and reported the nutritional qualities of different Dioscorea species, as shown in Table 1 and Table 2 . The nutritional abundance of yam varies depending on the species and variety, as well as the environmental conditions and agricultural practices engaged during planting [ 35 , 36 ]. The analytical method used for estimation also plays a significant role in nutritional levels recorded in yam.…”
Section: Yam Nutritional Valuementioning
confidence: 99%